Preoperative calcitonin testing improves the diagnosis of medullary thyroid carcinoma in female and male patients. Issue 2 (6th January 2022) - Weber, Theresia; Poplawski, Alicia; Vorländer, Christian; Dotzenrath, Cornelia; Ringelband, Rolf; Schabram, Jochen; Passler, Christian; Zielke, Andreas; Schlegel, Nicolas; Nies, Christoph; Krenz, Detlef; Jähne, Joachim; et al.
Abstract: Aim: Calcitonin (Ctn) measurement in patients with thyroid disease could potentially increase the detection rates of medullary thyroid carcinoma (MTC) but remains a controversial issue. The aim of this study was to evaluate routine preoperative Ctn measurements. Methods: All patients with thyroid surgery documented in the prospective StuDoQ|Thyroid registry between March 2017 and September 2020 were included. Cutoff levels for Ctn were determined with receiver-operating characteristic analyses to assess the preoperative diagnosis of MTC in subgroups for females and males. Findings: In 29 590 of 39 679 patients (75%) participating in the registry, routine preoperative Ctn testing was performed. In 357 patients (227 females and 130 males), histopathology confirmed MTC with a mean tumor size of 14.7 mm (±12.43). Biochemical cure was achieved in 71.4% of the patients. Ctn levels between 11 and 20 pg/mL were seen in 2.6% of the patients, and only 0.7% of the patients had Ctn levels above 21 pg/mL. Cutoff levels for the diagnosis of MTC were 7.9 pg/mL for females and 15 pg/mL for males ( P   < 0.001). The sensitivity and specificity for females were 95 and 98%, and 96 and 97% for males, respectively. Conclusion: Routine Ctn testing is a reliable predictor for MTC and provides the opportunity for earlier thyroidectomy before lymph node metastases occur, resulting in a better prognosis. Females with Ctn levels >7.9 pg/mL and males >15 pg/mL without any other extrathyroidal sources for an elevated Ctn should be monitored. Thyroid surgery should be considered if Ctn levels are increasing or ultrasound detects suspicious thyroid lesions.